2009
DOI: 10.1038/ki.2009.159
|View full text |Cite
|
Sign up to set email alerts
|

Fluid accumulation, survival and recovery of kidney function in critically ill patients with acute kidney injury

Abstract: Fluid accumulation is associated with adverse outcomes in critically ill patients. Here, we sought to determine if fluid accumulation is associated with mortality and non-recovery of kidney function in critically ill adults with acute kidney injury. Fluid overload was defined as more than a 10% increase in body weight relative to baseline, measured in 618 patients enrolled in a prospective multicenter observational study. Patients with fluid overload experienced significantly higher mortality within 60 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
678
8
19

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 937 publications
(744 citation statements)
references
References 13 publications
25
678
8
19
Order By: Relevance
“…Similar patterns of association with mortality have been reported in studies from South America (15) and Canada (14). Greater degrees of volume overload have been associated with a higher risk of adverse outcomes, including greater risk of 60-day mortality (24,25), longer duration of ventilator dependence (18,26), and slower recovery of renal function in those with AKI requiring RRT (19). Of note, although no randomized studies have been implemented to test if earlier initiation of RRT for volume control is beneficial (because volume removal by RRT may be offset by decreases in urine output), there is biologic plausibility to suggest that preservation of urine output may be a reasonable clinical management goal.…”
Section: Discussionsupporting
confidence: 59%
“…Similar patterns of association with mortality have been reported in studies from South America (15) and Canada (14). Greater degrees of volume overload have been associated with a higher risk of adverse outcomes, including greater risk of 60-day mortality (24,25), longer duration of ventilator dependence (18,26), and slower recovery of renal function in those with AKI requiring RRT (19). Of note, although no randomized studies have been implemented to test if earlier initiation of RRT for volume control is beneficial (because volume removal by RRT may be offset by decreases in urine output), there is biologic plausibility to suggest that preservation of urine output may be a reasonable clinical management goal.…”
Section: Discussionsupporting
confidence: 59%
“…Observational studies have identified several risk factors for non-recovery 48,[111][112][113][114][115][116][117] (see Supplementary information S5 (table)). Novel modalities that might enhance the prediction of non-recovery, including urine and plasma biomarkers, histopathologic markers on kidney biopsy specimens and imaging tools, should be carefully studied (BOX 6).…”
Section: Consensus Statement 3ementioning
confidence: 99%
“…[82][83][84][85] Recent data extend these findings to critically ill children and adults independent of renal replacement therapy. [86][87][88] The impact of fluid overload is highlighted in the practice guidelines proposed by the American College of Critical Care Medicine for pediatric and neonatal septic shock, which recommend that interventions to address fluid balance are warranted when critically ill children amass 10% volume overload. 89 Limited data are available on fluid overload in neonates.…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%